A new level set numerical wave tank with improved density interpolation for complex wave hydrodynamics. (25th November 2016) - Bihs, Hans; Kamath, Arun; Alagan Chella, Mayilvahanan; Aggarwal, Ankit; Arntsen, Øivind A.
Highlights: A new level set based numerical wave tank. High-order discretization for accurate modeling of wave hydrodynamics. Improved density interpolation for improved stability and accuracy. Very good numerical results for non-breaking waves. Breaking wave kinematics are fully captured. Abstract: A new three-dimensional numerical wave tank is developed for the calculation of wave propagation and wave hydrodynamics by solving the incompressible Navier–Stokes equations. The free surface is modeled with the level set method based on a two-phase flow approximation, allowing for the simulation of complex phenomena such as wave breaking. The convection terms of the momentum and the level set equations are discretized with the finite difference version of the fifth-order WENO scheme. Time stepping is handled with the third-order TVD Runge–Kutta scheme. The equations are solved on a staggered Cartesian grid, with a ghost cell immersed boundary method for the treatment of irregular cells. Waves are generated at the inlet and dissipated at the numerical beach with the relaxation method. The choice of the numerical grid and discretization methods leads to excellent accuracy and stability for the challenging calculation of free surface waves. The performance of the numerical model is validated and verified through several benchmark cases: solitary wave interaction with a rectangular abutment, wave forces on a vertical cylinder, wave propagation over a submerged bar and plunging breaking waves on a sloping bed.